Desenvolvimento e caracterização de nanocompósitos biodegradáveis a base de concentrado proteico de soro de leite / montmorilonita / licopeno - Pereira, Rafaela Corrêa (2015)
In the present study, the production and characterization of nanocomposites based on whey protein concentrate (WPC) and montmorilonite (MMT) incorporated of lycopene as functional substance is presented and discussed as an alternative biomaterial for potential uses in foodstuff applications. A full factorial design with varying levels of MMT (0 and 2% in w/w) and lycopene (0, 6 and 12% in w/w) was used. Optical properties (CIELab parameters, light transmission and film transparency), moisture, density, solubility, water vapour permeability, FTIR, antioxidant activity, mechanical properties (tensile and puncture tests) thermal stability analysis (DSC and TGA) and film morphology (MEV and AFM) of the resulting materials were evaluated. Results indicated that lycopene and MMT nanoparticles were successfully included in WPC films using the casting/evaporation method. The films were flexible and homogeneous and a uniform dispersion of the components were achieved. Inclusion of 2% w/w of MMT in the polymeric matrix significantly improved barrier property against water vapor and mechanical and thermal properties of the films. Lycopene, besides its good red coloring ability provided to the films antioxidant activity and protection against UV-vis light. These findings open a new perspective on the use of materials for bioactive packaging applications.